Pengaruh Penerapan Absensi Fingerprint dan Insentif Terhadap Kinerja Karyawan di Perhotelan - Antal Azizul Yamin; Mgs.M.Farhan Bintang Ramadhan; Iksan Ramadhan; Meike Revita Liza; Tasya Febriyanti; Edo Abyuhdani; Irma Idayati; Hardi Mulyono (Comit: Communication, Information and Technology Journal, 2025)
This research aims to examine the effect of implementing a fingerprint attendance system and providing incentives on employee performance in the hotel industry. The fingerprint attendance system is used to increase accuracy and efficiency in managing employee working time, while incentives function as motivation that can encourage increased work morale and productivity. This research uses a quantitative approach with a survey method involving employees at several hotels as respondents. The data collected was analyzed using multiple regression analysis to see the extent to which these two variables influence employee performance. The research results show that implementing a fingerprint attendance system has a significant effect on increasing punctuality and operational efficiency, while providing incentives is proven to increase motivation and job satisfaction which leads to better performance. Overall, implementing fingerprint attendance and providing incentives simultaneously can improve employee performance in the hotel industry. These findings suggest that hotel management needs to integrate an effective attendance system and appropriate incentive strategies to maximize productivity and service quality.